2013
DOI: 10.1517/14728222.2014.859248
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channel 1a-mediated calcium influx regulates apoptosis of endplate chondrocytes in intervertebral discs

Abstract: ASIC1a activation in endplate chondrocytes may trigger Ca(2+)-dependent proteases activity and signaling, which leads to apoptosis of endplate chondrocytes in IVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 48 publications
3
55
0
Order By: Relevance
“…18,19 To Exo, respectively, Figure 2E) in the purified EVs, consistent with the character of Abs. 18,19 To Exo, respectively, Figure 2E) in the purified EVs, consistent with the character of Abs.…”
Section: Oxidative Stress Increases the Generation Of Apoptotic Bodsupporting
confidence: 79%
See 1 more Smart Citation
“…18,19 To Exo, respectively, Figure 2E) in the purified EVs, consistent with the character of Abs. 18,19 To Exo, respectively, Figure 2E) in the purified EVs, consistent with the character of Abs.…”
Section: Oxidative Stress Increases the Generation Of Apoptotic Bodsupporting
confidence: 79%
“…Increased oxidative stress can induce chondrocyte apoptosis. 18,19 To determine the impact of oxidative stress on the production of Abs, endplate chondrocytes were treated with, or without, H 2 O 2 for varying time periods and the secreted EVs in the cultured cells were purified. As shown in Figure 2A Exo, respectively, Figure 2E) in the purified EVs, consistent with the character of Abs.…”
Section: Oxidative Stress Increases the Generation Of Apoptotic Bodmentioning
confidence: 99%
“…32 It was reported that ASIC1a played an important role in the pathogenesis of diseases associated with ischaemic injury, including strokes, retinal ischaemia, etc. 32 It was reported that ASIC1a played an important role in the pathogenesis of diseases associated with ischaemic injury, including strokes, retinal ischaemia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ASIC1a induces Ca 2+ entry and leads to intracellular Ca 2+ overload, which is a primary factor that causes cell apoptosis. 32 It was reported that ASIC1a played an important role in the pathogenesis of diseases associated with ischaemic injury, including strokes, retinal ischaemia, etc. 4,18,[33][34][35] In the present study, we found that blocking ASIC1a is protectable to renal ischaemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focusing on the effect of acid on chondrocytes have revealed an important role of acid-sensing ion channels (ASICs) (57,58). ASICs are a superfamily of amiloride-sensitive cationic channels and have six subunits: ASIC1a, ASIC1b, ASIC2a, ASIC2b, ASIC3, ASIC4.…”
Section: Acidic Stressmentioning
confidence: 99%